Content Analysis of Vocational High School Websites in the City of Padang - Roni Arya Gunawan; Agung Rorhi Prayudha; Rifa Rahayu Sartika (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2022)
A good school website is not only seen from the design side but, what is more important, from the content available whether it can provide useful information for the school community and other parties who need information about the school. So far, there are no standard guidelines and rules for creating website content for Vocational High Schools (SMK). Therefore, this study aims to investigate the content quality of SMK websites in the city of Padang. This research is qualitative, namely to analyze the availability of content criteria on the website of Vocational High Schools (SMK) in West Sumatra Province. The methods used in this research are content analysis and surveys. Researchers took samples from SMK in Padang City with 27 schools in this study. This research resulted in investigative data that the SMK websites in Padang City mostly used official domains. However, the average criteria for SMK websites in Riau Province were still standard. Still, content that links to the school's business and industrial world only gets a score of 33%, indicating the school still needs to update content regularly.